A PROSPECTIVE OBSERVATIONAL STUDY ON PATTERN OF ADVERSE DRUG REACTION TO ANTIBIOTICS COMMONLY PRESCRIBED IN THE HOSPITALIZED PEDIATRIC PATIENTS - Velraj, Malarkodi; V, MOHAN BABU (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Antibiotics are the almost usually specified or authorized medication in hospitals, and antibiotics were found to be the almost bothersome classes of drugs providing or endowing to adverse drug reactions (ADRs). Therefore, the present study was conducted to check or regulate the precautions (ADRs) of antibiotics usually specified or authorized in the pediatrics unit. Methods: A potential, experimental, non-interventionist study was conducted or executed in the Department of Pediatrics for a time of 6 months to analyze the ADRs reported spontaneously from the hospital using patient statistics, objective and medication information, data of ADRs, onset time, causal drug details, outcome, and severity. Results: Among 72 ADRs observed, beta-lactams and quinolones were set up to be contributing the highest number of ADRs. The duct or abdominal system was the almost commonly affected organ, followed by respiratory system and the cardiovascular system. The assessment by the World Health Organization causation estimation scale demonstrated that 5.56% ADRs were certain, 55.56% were possible, 30.56% were probable, and 8.33% were unlikely. Conclusion: Thus, the pattern of ADRs occurring in the pediatric population was observed and assessed. Early recognition and management of ADRs are essential to reduce the burden of ADRs